Occupational English writing test for potential nurses in Kuantan Pahang - Jebunnesa (2014)
Nursing is a noble profession which is evergreen and ever broadening in duties and demands. Highly expert nurses are always in good demand both locally and globally. As nursing is being globalised significantly, a command in English has grown to be an essential requirement for health practitioners in all areas of the profession especially in diverse context. Malaysia is a highly multi-cultural and multi-linguistic country but nurses in Malaysia are not required to sit for any specific English Language test that suits the medical setting. At the moment the existing English Language tests do not specifically test nurses to use English Language in the context of medical situation. This research aims to suggest a special test, the Occupational English Writing Test (OET) which is specifically designed for health practitioners. Specifically the objectives of this research are to assess Malaysian nurses' performance in the OET, to evaluate the suitability and acceptability of the OET in Malaysian context. The OET is a language test used to assess health practitioners' English Language proficiency in medical and health context. It is designed to ensure that language competency is assessed in a relevant professional context. This study employs a case study. The nurses chosen as samples for this research cover 7 nurses of Medical Centre UMP and a group of nursing students from Kolej Kejururawatan, Kuantan and University College Shahputra, Kuantan. The researcher administers a questionnaire which comprises of three OET original sample writing tests. She also interviews the samples individually after the test. The test results are analyzed manually based on three variables. The result of this study which is conducted by OET sample writing test and especially the interviews obviously signifies that nurses' lack of communication skill is a barrier to patient safety. Therefore the nurses need to demonstrate a good communication skill in working context. Thus their language proficiency needs to be tested and OET is suitable for this purpose because OET exemplifies the real difficulty of language performance of health practitioners in work-related context. From the research, it is also crystal clear that OET is very much acceptable to Malaysian nurses. So by implementing OET on the nurses, Malaysia can produce highly skilled and •linguistically competent nurses who can mitigate the risk of health services due to inadequate English language skills and can also work in abroad.